Environmental control of phosphogypsum and tars of Rozdil State Mining and Chemical Company "Sirka" - Dzhumelia, Elvira; Pohrebennyk, Volodymyr (Lviv Polytechnic Publishing House, 2015)
The purpose of this work is the environmental control of phosphogypsum and tars of Rozdil State Mining and Chemical Company "Sirka", definition of soil pollution in the area.